Cohesion policy at the interface between regional development and the promotion of innovation - Knut Koschatzky; Thomas Stahlecker (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
Taking the implications of the cohesion policy framework for innovation governance as a starting point, it is the objective of this paper to discuss challenges for regional policy making with regard to a policy mix that is new to regional policy makers. Based on two German regions representing convergence and competitive and employment regions it will be discussed how regional policy makers can deal with this new policy approach and what could be appropriate strategies, programmes and learning tools. What can be seen from both the Bavarian and the Saxon case study is that the two regions apply a broad mix of different innovation policy measures, supporting all innovation policy tasks with relevance to regional development. In both regions innovation policy is not a new task, but Saxony as well as Bavaria can look back to a quite long tradition in the im-plementation of this policy. Differences exist with regard to policy learning in a way that due the longer innovation policy experiences of Bavaria more sophisticated structures and activities can be found in this federal state.
urn:nbn:de:0011-n-971174
Keywords: 330; Regionalpolitik; Innovationspolitik; Regionale Entwicklung; Bayern; Sachsen